Oxidation of propyl paraben by ferrate(VI): Kinetics, products, and toxicity assessment. Issue 10 (24th August 2018) - An, Jibin; Xia, Chunqiu; He, Jiahong; Feng, Huixia
ABSTRACT: Propyl paraben (propyl 4-hydroxybenzoate, PPB), one of the typically used paraben species in various pharmaceutical and personal care products, has been found in different aquatic environment, which could affect the water quality and human health. In this paper, the degradation of PPB by aqueous ferrate (Fe(VI)) was investigated in different water matrix and reaction kinetics as a function of pH was determined. Intermediate products of the degradation process were isolated and characterized by the high performance liquid chromatography/mass spectrometry/mass spectrometry techniques. Acute and chronic toxicities during water treatment of PPB using Fe(VI) were calculated using the ECOSAR program at three trophic levels. The obtained apparent second-order rate constant ( k app ) for PPB reaction with Fe(VI) ranged from 99.6 ± 0.4 M −1 s −1 to 15.0 ± 0.1 M −1 s −1 with the half-life (t1/2 ) ranging from 154 s to 1026 s at pH 6.5–10.0 for an Fe(VI) concentration of 600 μM. The proposed pathway for the oxidation of PPB by Fe(VI) involves one electron transfer of phenoxyl radical and breaking of the ether bond. In general, the oxidation of PPB by ferrate resulted in a significant decrease in toxicity at three trophic levels.